Futsal As a Means of Improving Women Football Players' Playing Skills : A Qualitative Assessment of Player Perceptions - Ramadhan, Muhamad Hanif; Fitri, Mustika; Sidik, Dikdik Zafar (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
The purpose of this study was to determine whether futsal could help improve playing skills for women football player. Some researchers claim that futsal can help in enhancing football playing skills. However, no studies have been conducted on women football player; the research was conducted on men's football players. Futsal was created as an indoor variant of football. With that in mind, it is fair to suggest futsal as many of the techniques and skills required are similar to football, such as controlling the ball, shooting, passing and shooting. This research is qualitative, data collection using open questions conducted through the google form application.The participants in this study were amateur women football player who had participated in futsal. This article wants to show that futsal can positively impact improving skills for women football player.